Afro-brazilian fashion sector: Concepts;Strucures and Narrative (ModaPalavra e-periódico, 2016)
The purpose of this article is to present the Afro-Brazilian fashion concepts and claims it as an effective market segment. Many people are unaware about this niche, but it operates in the fashion market carrying the pillars of our culture. To strengthen this research, twenty brands that develops the Afro-Brazilian fashion were analyzed and how they are connected with this culture related to its colors, styles and structures. The research is based on the fundamentals of the relationship between the identityof the segment's representatives stylists and fashion.
Keywords: Afro-Brazilian; fashion segment; fashion designers